1993
DOI: 10.1177/41.1.8417112
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-amplified immunohistochemistry.

Abstract: We describe a novel technique for improving the sensitivity of immunofluorescence staining by use of ultrasonic irradiation. Free-floating vibratome sections from rat cerebellum were incubated with primary antiserum and simultaneously were briefly exposed to ultrasound (US) in a conventional ultrasound bath. After the US treatment, a conventional immunohistochemical method was employed. Two different antisera and two conventional immunohistochemical detection systems were tested. In all cases a 10-20-sec US tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…To enhance antigen penetration, an ultrasound-amplified immunostaining method was used (54). Briefly, after incubation of the samples with normal blocking serum, ultrasound irradiation was carried out with the primary antiserum (1:3,000 in PBS-1% normal goat serum) in an ultrasound bath for 20 s, thereafter incubated with the same solution overnight at 4°C, and further processed for antigen visualization as described above.…”
Section: Methodsmentioning
confidence: 99%
“…To enhance antigen penetration, an ultrasound-amplified immunostaining method was used (54). Briefly, after incubation of the samples with normal blocking serum, ultrasound irradiation was carried out with the primary antiserum (1:3,000 in PBS-1% normal goat serum) in an ultrasound bath for 20 s, thereafter incubated with the same solution overnight at 4°C, and further processed for antigen visualization as described above.…”
Section: Methodsmentioning
confidence: 99%
“…16 Since the 1960s, a few groups have reported using ultrasound to increase the speed of fixation 17 and processing 18,19 and to accelerate immunoassay 20,21 and staining. 22 Most of these studies used commercially available ultrasound generators and involved the use of low-frequency ultrasound (approximately 40 kHz), which led to controversial results and frequent tissue damage.…”
mentioning
confidence: 99%
“…9,31 The physical process of opening holes or channels within the tissue section also likely explains the modest success of ultrasonics as an AR method. 92 Successful application of heat -induced AR requires regulation of the pH of the recovery buffer. Shi et al 31,93 found three patterns of pH dependence as judged by immunostaining: (1) antigen recovery is independent of pH (stable type), (2) antigen recovery improves with increasing pH (ascending type), and (3) optimal antigen recovery occurs at low or high pH (V -type).…”
Section: General Comments On the Mechanism Of Armentioning
confidence: 99%